The Investigation of The Relationship Between Perfectionism and Creative Thinking Dispositions - Uğur Akpur (Istanbul Kültür University, 2024)
The multidimensional nature and the psychological aspects of perfectionism suggest that creativity could be affected by the two sides of perfectionism differently. The purpose of the current study is to explore the potential predictive powers of adaptive and maladaptive perfectionism on creativity. The study group consisted of 151 college students attending a university in İstanbul. The APS Perfectionism Scale and The Marmara Creative Thinking Dispositions Scale were administered to the participants as data collection tools. The findings revealed that there is a positive and significant relationship between adaptive perfectionism and creativity. On the other hand, the relationship between maladaptive perfectionism and creativity as well as the relationship between maladaptive perfectionism and adaptive perfectionism is significant and negative. In the regression analysis it was found out that the adaptive perfectionism predicts creativity positively and significantly (ß=.40; p<0.01), while maladaptive perfectionism predicts creativity significantly in a negative way.